Chemoprotection of ethylene glycol monoethyl ether-induced reproductive toxicity in male rats by kolaviron, isolated biflavonoid from Garcinia kola seed (2012)
"The present study investigated the protective effect of kolaviron, a biflavonoid from the seed of Garcinia kola, on ethylene glycol monoethyl ether (EGEE)–induced reproductive toxicity in male rats. The protective effect of kolaviron was validated using vitamin E, a standard antioxidant. EGEE was administered at a dose of 200 mg/kg. Other groups of rats were simultaneously treated with kolaviron (100 and 200 mg/kg) and vitamin E (50 mg/kg) for 14 days. EGEE treatment resulted in significant decrease in glutathione (GSH) level, superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) activities but markedly increased the glutathione-Stransferase (GST) and lactate dehydrogenase (LDH) activities in the testes. In the spermatozoa, administration of EGEE caused significant decrease in the activities of CAT, GPx, GST and LDH as well as in the level of GSH but significantly increased SOD activity with concomitant increase in hydrogen peroxide and malondialdehyde levels in both testes and spermatozoa. EGEE-exposed rats showed marked testicular degeneration with concomitant decrease in spermatozoa quantity and quality. Overall, EGEE causes reproductive dysfunction in rats by altering antioxidant systems in the testes and spermatozoa. Kolaviron or vitamin E exhibited protective effects against EGEE-induced male reproductive toxicity by enhancement of antioxidant status and improvement in spermatozoa quantity and quality.